Thermo-Responsivity of the Polyacrylate-Adsorbed Metal Cation and its Hydration Structure - Yoshimi Seida; Takahiro Imai; Kiyoshi Murata; Yoshio Nakano (Adsorption Science & Technology)
The thermo-responsive phase behaviour of the sodium salt of poly(acrylic acid) (PAA) was studied when its counter-ion was exchanged for a series of metal cations (PAA–metal cation complexes). The thermo-responsivity of such PAA–metal cation complexes appeared greatest for divalent metal cations capable of interacting weakly with PAA carboxylates. The thermo-responsivity was correlated with the adsorption behaviour of PAA towards such cations and the hydration structure of the complexes. The effect of metal cations on the thermo-responsivity followed the Irving–Williams order of stability. The condition of such complexes allowing the generation of thermo-responsivity was discussed.